Memaksimalkan Potensi Studentpreneur di Lingkungan Universitas Respati Yogyakarta (UNRIYO) melalui Pembinaan Manajemen Keuangan, Manajemen Sumber Daya Manusia (SDM), dan Pelatihan E-Marketing - Wulandari, Novi; Rahmayanti, Dian Rhesa; Susanti, Dwi Lisa; Rohmah, Khaula Lutfiati; Iskandar, Metty; Nugroho, Setyo Mahanani (Universitas Respati Yogyakarta, 2019)
Studentpreneur, can be simply interpreted as an entrepreneurial student. As a university that values entrepreneurship in its vision, Respati Yogyakarta University (UNRIYO) has applied entrepreneurship as a compulsory subject in each study program which not only contains theory, but also applies the entrepreneurship practice. By the entrepreneurship courses, it is expected that the entrepreneurship spirit within the students is well-formed and developed. However, in fact, based on the results of the team survey, the number of studentpreneur is still less than 5%. Based on the observation done by the team, it is known that there are three subjects faced by the studentpreneur, namely: 1) lack of skill in financial management; 2) lack of skill in managing human resources; and 3) lack of skill in doing promotion by utilizing media.Â To overcome the student's problems, the team took the initiative to hold a workshop on financial management, human resource management, and e-marketing which was held on April 28, 2018. The workshop was attended by 60 students, consisting of students who already run the business and / or students who are interested in doing business. In addition to being equipped with theories on financial management, human resource management, and e-marketing, the workshop participants were also asked to create a simple business plan in groups and present the results. From these activities, it is known that students have creative ideas in building a business which is able to compete in the market.Keywords: Studentpreneur, Entrepreneurship, Financial Management, Human Resource Management, E-marketing